Anti-HBs positive occult hepatitis B virus carrier blood infectious in two transfusion recipients - Levicnik-Stezinar, Snezna; Rahne-Potokar, Urska; Candotti, Daniel; Lelie, Nico; Allain, Jean-Pierre (Journal of hepatology, 2008)
Occult hepatitis B infection (OBI) in blood donations is not considered infectious when anti-HBs is present. Four months after transfusion of eight blood components during coronary arterial bypass surgery, a 59-year-old patient developed acute hepatitis B. A second 71-year-old patient transfused with a red cell concentrate (RCC) from one of these donations had early HBV infection 7months post-transfusion. Samples were tested for HBV serological markers and HBV DNA was quantified and sequenced. One implicated donation contained anti-HBc, anti-HBs (12 IU/L) and 180IU/ml of HBV DNA. Previous and subsequent samples contained 3–10 times lower viral load and slightly variable anti-HBs. Two previous donations did not cause HBV infection. Recipients of the FFP and RCC from the index donation were both HBV infected and carried genotype D strains with sequences identical to the donor strain. Despite anti-HBs, an OBI carrier transmitted HBV to two immunocompetent transfusion recipients.